DEVELOPMENT OF FREE ECONOMIC ZONES (Conferencea, 2022)
The world experience of organizing free economic zones allows us to draw certain conclusions about their general achievements, general characteristics and specific aspects of their development. Free economic zones in industrialized countries depend on good planning and flexible management.